Comparison Of Bacillus anthracis Prepared Used Antigens As ‎Diagnostic kit Of Anthrax In Laboratoy Animals.‎ - A.J. ‎, Al- Jebouri; G.M.‎, Al- Khatib (The Iraqi Journal of Veterinary Medicine, 2007)
This study was concerned on the preparation of several antigens on different types of culture media like brain heart infusion, tryptic soy agar and broth. A comparison was carried out among the prepared antigens using skin test in non- vaccinated guinea pigs which showed negative results. Another trials were conducted using sensitized guinea pigs with live attenuated anthrax vaccine. After three weeks of immunization, skin test was conducted and all antigens revealed positive skin reactions. The highest means were recorded by the dilution 1/40 on the brain heart infusion agar with the mean of erythema of 16.38 mm and a difference of thickness 3.44 mm, while on tryptic soy broth the mean of erythema was 14.14 mm and the difference of thickness was 3.43 mm. The mean of erythema and thickness were 10.21 mm and 2 mm subsequently observed on the dilution 1/40 on tryptic soy agar. The antigen gained from brain heart infusion gave a mean of erythema of 9.5 mm and 3.02 mm thickness. The results mentioned above indicated that the best antigens for the diagnosis and evaluation of anthrax vaccines are the antigen prepared on tryptic soy broth and the two diluted antigens as well.